using elimination method solve the equation 7(a+b) = 7(y-x) 5(3x-y) = x+3

Question

using elimination method solve the equation
7(a+b) = 7(y-x)
5(3x-y) = x+3

in progress 0
Alice 1 week 2021-11-25T18:43:41+00:00 1 Answer 0 views 0

Answers ( )

    0
    2021-11-25T18:44:51+00:00

    Answer:

    see the explanation

    Step-by-step explanation:

    we have

    7(a+b)=7(y-x)

    simplify

    (a+b)=(y-x) —–> equation A

    5(3x+y)=x+3

    15x+5y=x+3\\14x+5y=3

    Rewrite

    3=14x+5y —–> equation B

    Solve by elimination method

    Multiply equation A by 14 both sides

    14(a+b)=14y-14x —–> equation C

    Adds equation B and equation C

    3=14x+5y\\14(a+b)=14y-14x\\-----------\\3+14(a+b)=5y+14y\\3+14(a+b)=19y

    y=\frac{3+14(a+b)}{19}

    Find the value of x

    substitute the value of y in the equation B

    3=14x+5(\frac{3+14(a+b)}{19})

    14x=3-5(\frac{3+14(a+b)}{19})

    x=\frac{3}{14}-\frac{5}{14}(\frac{3+14(a+b)}{19})

Leave an answer

45:7+7-4:2-5:5*4+35:2 =? ( )